Dynamic adaptation of delayed time of diffusion of emergency messages in cognitive vehicular networks - J.U. Avalos Gómez; E. Stevens-Navarro; U. Pineda-Rico; M. Cárdenas-Juárez; A. Arce; S. González (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This article presents a protocol for the dissemination of emergency safety messages that uses a dynamic adaptation of the delay time in the environment of a cognitive vehicular network. The scenario studied considers the spectrum sharing between the band for vehicular communications and the digital television band with the objective of mitigating the effects of the diffusion storm on a vehicular network. Two of the most commonly used diffusion mitigation techniques in the literature are compared against the proposed protocol in terms of the probabilities of reachability of emergency messages and channel occupancy. The numerical results show that the protocol with the dynamic adaptation of the time presents a better performance in conditions of high density of vehicles, which is characteristic of a diffusion storm scenario.